Ethnobotany and Potential of Suruhan (Peperomia pellucida) as a Herbal Medicine Ingredient - Rovik, Anwar; Afifah, Laelatul; Rokhmalia, Nur; Andyra, Vania Uly (Universitas Karya Husada Semarang, 2024)
Background: People have long utilized various herbs for traditional medicine, including the suruhan or sirih cina plant (Peperomia pellucida). This plant is known by numerous local names such as rumput cacing, sirih bumi, pansit-pansitan, rumput gelas, and daing siheah cino. It is widely distributed in tropical and subtropical regions, including Indonesia, making the raw materials easily accessible for herbal medicine. Objective: This study aims to review the ethnobotany and the pharmacological potential of Peperomia pellucida as a natural ingredient for herbal medicine. Methods: This article is a narrative review that synthesizes various literatures regarding the traditional uses, phytochemical content, and biological activities of the suruhan plant. Results: The suruhan plant is used in traditional medicine through various preparation methods depending on the ailment, with the leaves being the most frequently utilized part. Phytochemical analysis reveals that it contains abundant bioactive compounds, including alkaloids, flavonoids, sterols, tannins, reducing sugars, amino acids, saponins, triterpenoids, carbohydrates, phenols, azulene, carotenoids, and quinones. These compounds contribute to its wide-spectrum antibacterial, antifungal, and anticancer activities. Conclusion: Peperomia pellucida holds significant potential as a herbal medicine ingredient due to its rich bioactive content and its long-standing history of traditional use. Accelerated industrial development and government support are needed to optimize its utilization in the healthcare sector.